Complex functionality with minimal computation: Promise and pitfalls of reduced‐tracer ocean biogeochemistry models. (21st December 2015) - Galbraith, Eric D.; Dunne, John P.; Gnanadesikan, Anand; Slater, Richard D.; Sarmiento, Jorge L.; Dufour, Carolina O.; de Souza, Gregory F.; Bianchi, Daniele; Claret, Mariona; Rodgers, Keith B.; Marvasti, Seyedehsafoura Sedigh
Abstract: Earth System Models increasingly include ocean biogeochemistry models in order to predict changes in ocean carbon storage, hypoxia, and biological productivity under climate change. However, state‐of‐the‐art ocean biogeochemical models include many advected tracers, that significantly increase the computational resources required, forcing a trade‐off with spatial resolution. Here, we compare a state‐of‐the art model with 30 prognostic tracers (TOPAZ) with two reduced‐tracer models, one with 6 tracers (BLING), and the other with 3 tracers (miniBLING). The reduced‐tracer models employ parameterized, implicit biological functions, which nonetheless capture many of the most important processes resolved by TOPAZ. All three are embedded in the same coupled climate model. Despite the large difference in tracer number, the absence of tracers for living organic matter is shown to have a minimal impact on the transport of nutrient elements, and the three models produce similar mean annual preindustrial distributions of macronutrients, oxygen, and carbon. Significant differences do exist among the models, in particular the seasonal cycle of biomass and export production, but it does not appear that these are necessary consequences of the reduced tracer number. With increasing CO2, changes in dissolved oxygen and anthropogenic carbon uptake are very similar across the different models. Thus, while the reduced‐tracer models do not explicitly resolve the diversity and internal dynamics of marine ecosystems, we demonstrate that such models are applicable to a broad suite of major biogeochemical concerns, including anthropogenic change. These results are very promising for the further development and application of reduced‐tracer biogeochemical models that incorporate "sub‐ecosystem‐scale" parameterizations. Key Points: We compare a family of functionally similar biogeochemical models with 3, 6, and 30 tracers Nutrient and gas simulations are similar across all three, under both preindustrial and rising CO2 Reduced‐tracer models can provide low‐cost yet complex biogeochemical simulations at high resolution